If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + -7 = -73 Reorder the terms: -7 + 6h = -73 Solving -7 + 6h = -73 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6h = -73 + 7 Combine like terms: -7 + 7 = 0 0 + 6h = -73 + 7 6h = -73 + 7 Combine like terms: -73 + 7 = -66 6h = -66 Divide each side by '6'. h = -11 Simplifying h = -11
| -1r=6 | | x^2y^2=2x | | ln(x)+5=0 | | (5)(-10)= | | x-8y=-11 | | 3x+4x+5x=90 | | 333x-54=7 | | 55x+5y=25 | | (13)(0)(-16)= | | 2(7-7x)=2x+4 | | 4p^2+7p-2=0 | | 2(7-7x)=2x-4 | | 114-2x=34x+18 | | p+6/3=4p+3/8 | | (-7)(4)(3)= | | 1/3(p-3)=114 | | (-5)(2)(-3)= | | 2(x-1)-4=-2 | | 6x^2+x^2-24x-4=0 | | 2x-1-4=-2 | | 2p+4q=12 | | 3x^2+12x=1 | | 2g^2-35g+17= | | 4x^2-16x+7= | | m^2-7m-18= | | 8m^3+14m^2-20= | | 5x+8y=55 | | -27+13= | | x-(-2)=-20 | | 21=4-r | | (7*x)-(3*y)-(4*x)-(2*y)= | | 6v^2-144+12v=0 |